Endothelial dysfunction in the first trimester of pregnancy - Alexey V. Mironov; Madina M. Umakhanova; Alexandr V. Zhukocky (IP Berlin A.V., 2020)
Relevance. Endothelial pathology is an important factor in the development of obstetric complications. Endothelial dysfunction means a violation of vascular homeostasis and leads to critical changes in the microcirculatory system. These changes in early pregnancy disrupt the processes of trophoblast invasion, determining obstetric complications. Aim. To improve the diagnosis of fetoplacental system disorders by examining endothelial function in the first trimester of pregnancy. Materials and methods. 180 pregnant women in the first trimester were examined: 90 women who were diagnosed with a failed miscarriage and had an instrumental removal of the fetal egg, as well as 90 somatically healthy pregnant women who had an instrumental abortion at will. Endothelial status was diagnosed in the groups: concentrations of C-reactive protein, von Willebrand factor and apoptosis protein p53 in serum, albumin in urine were determined, and desquamated endothelial cells were counted in peripheral blood. After instrumental removal of the fetal egg in all pregnant women studied, morphometry of fetal chorion vessels was performed: the average wall thickness of the primary vessel, the average diameter of the vessel lumen, the average area of the vessel lumen, and the Kernohan index were determined. The obtained results were subjected to statistical analysis. Conclusions. The study of endothelial function in the first trimester of pregnancy can be used as a test for detecting vascular disorders in pregnant women, being an important criterion for early diagnosis of obstetric complications.